Біортогональні системи розв’язків рівняння Гельмгольца в циліндричній системі координат - Сухорольський, М. А.; Достойна, В. В.; Веселовська, О. В.; Sukhorolsky, M. A.; Dostoina, V. V.; Veselovska, O. V. (Видавництво Львівської політехніки, 2018)
Побудовано систему розв’язкiв рiвняння Гельмгольца у цилiндричнiй системi координат у виглядi однорiдних полiномiв за двома бiортогональними системами функцiй.

We construct the system of solutions of the Helmholtz equation in cylindrical coordinates in the form of homogeneous polynomials by two biorthogonal systems of functions.
Biorthogonal systems solutions of the helmholtz equation in a cylindrical coordinate system
Keywords: рiвняння Гельмгольца; однорiднi полiноми; бiортогональнi системи функцiй; Helmholtz equation; homogeneous polynomials; biorthogonal system of functions; 517.53.57